Qualidade de vida da equipe de enfermagem de uma unidade de pronto atendimento na cidade de Bauru - Beijo, Priscila Batista (2019)
Introduction: The National Policy On Emergency Care (PNAU) was established by the Brazilian Ministry of Health (MS) in 2003, aiming to guarantee universality, equity and integrality in emergency care. The Emergency Care Units (UPA) were created to function as a gateway to the services of urgent care that, depending on the case, could be solved on the spot, stabilized and/or forwarded to hospitals or redirected to the UBS. Objective: to assess the quality of life of the nursing staff of a Emergency Care Unit in the city of Bauru. Methodology: through the WHOQOL-100 questionnaire that consists of one hundred questions referring to six aspects: physical, psychological, level of independence, social relations, environment and spirituality/religiosity/personal beliefs. Results: The interviews took place in the period from March to April 2019 and indicated averages between 55.6 (physical domain) and 80.0 (Spirituality/religiosity domain/personal beliefs). The minimum values were in the range 32.8 (Environment domain) and 50.0 (Spirituality/religiosity domain/personal beliefs), as well as the maximum covered scores between 74.0 and 100.0 for the same domains. Conclusion: The quality of life of the nursing team is considered reasonable/good. The physical domain has the lowest average found of 55.6, evidencing a discontent with this factor, and the highest average found in the domain Spirituality/religiosity/personal beliefs of 80.0, therefore, the nursing team appears strengthened in their spiritual issues and their beliefs.